Evaluating Influence of Nonlinear Disturbances on Image Registration Based on Virtual Forces - Stern, Claudius; Kleinjohann, Lisa (Proceedings of The 2nd International Conference on Intelligent Systems and Image Processing 2014)
In case of a disaster it is of utmost importance to obtain an overview of the affected area in order to coordinate rescue operations. Recent research and development has led to affordable unmanned aerial vehicles (UAVs) and enabled (semi-)autonomous surveillance and mapping of a disaster areas by UAVs. Mapping an area from many images incorporates image registration. Commonly used registration techniques expect static images to be registered. However, while mapping a disaster area, it is very likely that objects like vehicles or persons are moving on the ground, thus leading to dynamic scenes. We formerly introduced a fast and robust approach to register large amounts of successively arriving images, e.g., from UAVs. The approach only uses rigid-body transformations, but the usage of virtual forces enables the registration to tolerate small perspective distortions. This paper investigates the performance of our approach when applied to dynamic scenes, which are represented by nonlinear disturbances within image correspondences. We show that our approach not only tolerates small perspective distortions but also is able to register dynamic scenes.

A Criticality-aware Mapping of Real-time Virtual Machines to Multi-core Processors - Grösbrink, Stefan; Almeida, Luis (19th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Virtual Platforms for Model-Based Design of Dependable Cyber-Physical System Software - Becker, Markus; Kuznik, Christoph; Müller, Wolfgang (17th Euromicro Conference on Digital Systems Design (DSD))

Towards Self-Reconfiguration of Real-Time Communication within Cyber-Physical Systems - Jatzkowski, Jan; Kleinjohann, Bernd (2nd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering (SysInt))

Efficient Integration of Online Model Checking into a Small-Footprint Real-Time Operating System - Sudhakar, Krishna; Zhao, Yuhong; Rammig, Franz-Josef (Proc. 2014 IEEE 17th International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing (ISORC))

Online Behavior Classification for Anomaly Detection in Self-X Real-Time Systems - Rammig, Franz-Josef; Stahl, Katharina (Object/Component/Service-Oriented Real-Time Distributed Computing (ISORC), 2014 IEEE 17th International Symposium on)

Combining Automatic Service Composition with Adaptive Service Recommendation for Dynamic Markets of Services - Jungmann, Alexander; Mohr, Felix; Kleinjohann, Bernd (Proceedings of the 10th World Congress on Services (SERVICES))

Virtual Machine Migration as a Fault Tolerance Technique for Embedded Real-Time Systems - Grösbrink, Stefan (8th IEEE International Conference on Software Security and Reliability)

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Jungmann, Alexander; Brangewitz, Sonja; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the Sixth International Conferences on Advanced Service Computing (SERVICE COMPUTATION))

EU-Forschungsprojekt AMALTHEA: Entwicklung einer open-source Entwicklungsplattform, erweiterbar durch die Community - Brink, Christopher; Jatzkowski, Jan (SafeTRANS News (1))